2005
DOI: 10.1007/s00330-005-2880-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical analysis of monitor display functions affecting observer diagnostic performance of CT image on liquid crystal display monitors

Abstract: The aim of the present study was to propose suitable display functions for CT image representation on liquid crystal display (LCD) monitors by analyzing the characteristics of the monitor's typical display functions using psychophysical analysis. The luminance of the LCD monitor was adjusted to a maximum of 275 cd/m2 and 480 cd/m2. Three types of postcalibrated display functions (i.e., GSDF, CIELAB, and Exponential gamma 2.2) were evaluated. Luminance calculation of a new grayscale test pattern (NGTP) was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…During the 1960s, Kanamori 3,4 proposed the psychophysical gradient δ, corresponding to visually recognized contrast, which can be used for inspection of perceptual linearization. In previous articles, [5][6][7] we confirmed the usefulness of applying δ to liquid crystal display (LCD) monitors. The objectives of the present work are (1) to compare, using ROC analysis, the suitability of the GSDF and CIE curves as calibration tools for clinical images and (2) to explain the relation between tumor detectability and visually recognized contrast using psychophysical analysis.…”
Section: Introductionsupporting
confidence: 55%
“…During the 1960s, Kanamori 3,4 proposed the psychophysical gradient δ, corresponding to visually recognized contrast, which can be used for inspection of perceptual linearization. In previous articles, [5][6][7] we confirmed the usefulness of applying δ to liquid crystal display (LCD) monitors. The objectives of the present work are (1) to compare, using ROC analysis, the suitability of the GSDF and CIE curves as calibration tools for clinical images and (2) to explain the relation between tumor detectability and visually recognized contrast using psychophysical analysis.…”
Section: Introductionsupporting
confidence: 55%
“…We must investigate the optimal viewing size for detecting n-GGOs from the viewpoint of the human visual system in the future. Third, other factors were not evaluated such as the display luminance and display function, which also influence observer performance [20][21][22][23]; however, GSDF is recommended as a standard display function for soft-copy diagnosis [24]. Fourth, we did not use a low-dose protocol for lung cancer CT screening.…”
Section: Discussionmentioning
confidence: 98%
“…Yamaguchi et al [11] reported that the display function combining gamma 2.2 and GSDF was ideal for the interpretation of brain CT images. In our study, the gray level of brain parenchyma was shown to be within a range where the image contrast on gamma 2.2 was higher than the one on GSDF, which suggested that the image contrast of a brain CT on a general-type LCD or notebook PC was better than one on a medical-grade LCD.…”
Section: Discussionmentioning
confidence: 99%